Masalah Oedipus Complex Dalam Novel Umibe No Kafuka Karya Haruki Murakami - Linda Unsriana (Lingua Cultura, 2011)
Haruki Murakami, a Japanese novelist is an example of a great novelist who has produced his works which have been translated in various languages for a variety of readers in the world. He has also been awarded the Yomiuri Literary Award for his novel Wind-up Bird Chronicle in 1996. In his novel Umibe no Kafuka, Murakami describes the life of a young man and the Oedipus complex problems he experienced. This study will look for root causes of problems in the Oedipus complex problem of Kafka Tamura, to analyze them through methods of role characterization.